Age Related Changes in Cardiovascular Response to Oxidative Stress Induced by Exercise - Hassen Al-Taai, Affan E.; El-Yassin, Hedef D. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: There are many circulatory changes that occur during exercise in order to supply the tremendous blood flow required by the muscles during the stimulatory effects on circulation by the mass sympathetic discharge, the increased arterial pressure and cardiac output. The metabolic effects and the oxidative stress as a result of the work load on cardiac and skeletal muscles could also show changes. Objective: This study was designed to investigate the effects of aging process on the vascular response during exercise and also in the oxidative stress according to age. Subjects and Methods: Eight healthy Iraqi subjects were enrolled in this study. Divided into three groups according to age, group I (age range 20-29), group II (age range 30-39), and group III (age range 40-49). They were asked to exercise according to modified Bruce protocol. Blood samples were taken from each subject pre and post exercise for biochemical tests. The test included were creatine kinase, uric acid, malonedialdehyde (MDA) , lipid profile (triglycerides, cholesterol, high density lipoprotein HDL). Low density lipoprotein LDL was calculated. Results: There is a statistical significance increase in heart rate and systolic blood pressure after exercise in all groups however diastolic blood pressure showed a decrease. A positive linear correlation is present. Mean serum levels of uric acid was shown to be elevated after exercise, meanwhile triglycerides levels decreased significantly in all age groups after exercise and also cholesterol. LDL on the other hand showed a decrease in the younger age group. Conclusion: The results obtained set a normative data for the studied parameters for the age group included in the study to be used in the future for the detection and differentiation of any cardiovascular abnormality from age related changes. These data have important clinical implications if we are to prevent the frailty and morbidity associated with old age.